Deteksi Dini dan Upaya Pengendalian Diabetes Milletus dan Hipertensi di Posbindu Ngudi Waras Jaten Karanganyar - Hastutik, Hastutik (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Degenerative diseases can occur due to changes in body cells that can affect overall organ function. Public awareness for early detection of degenerative diseases needs to be increased. Hypertension and diabetes mellitus are degenerative diseases that need to be monitored and detected as prevention efforts. This prevention effort can be done before or after someone is diagnosed with a disease. The purpose of this community service is to check blood pressure and blood glucose at Posbindu Ngudi Waras as an effort to detect degenerative diseases early. There were 35 participants who took part in this activity, from the results of the examination it was found that 16 people suffered from high blood pressure and 2 people who had blood glucose levels above normal. The results of checking blood pressure and blood sugar levels on a regular basis is a technique that can be used to detect degenerative diseases.